Uma leitura valorativa do “fresh start” na legislação brasileira como meio de superação de obstáculos e solução para a célere reabilitação do falido - Tauk, Clarissa Somesom (2023)
The research searchs to make a diagnosis on the rehabilitation of the insolvent agent considering what currently exists in Brazilian legislation. From the study of the subject, the research intended to answer whether the “fresh start” mechanisms elected by Brazilian legislation are really effective in practice to make it possible for the bankrupt fase to return to the market, recognizing him free of obligations. It seems that, despite the recent reform implemented by law 14.112/20, the Brazilian legal system still presents some obstacles to the full rehabilitation of the insolvent agent, through the total extinction of their obligations. Would Brazilian entrepreneurs rather submit to the uncertainties of irregular closure than the system of bankruptcy? With this in mind, the thesis sought to identify the obstacles to the rehabilitation of the agent and possible ways of overcoming these obstacles. To this end, a doctrinal and critical comparative reading of international legislation - with a focus on the United States - was carried out in order to corroborate the thesis of a systematic legislative interpretation that takes into account the value ideas of the bankruptcy system, in order to achieve a constitutional interpretative alliance on the subject, under the aegis of human dignity as a transgressive solution to the obstacles. From this perspective, this thesis aims to study the values enshrined in the Brazilian insolvency system and their harmonious correlation with fundamental rights, choosing the fresh start as an important instrument for the realization of human dignity and the protection of fundamental rights. The aim is to demonstrate that the fresh start is in harmony with the ideals and values enshrined in humanist capitalism, represented by human rights protection rules that permeate the constitutional text. To this end, the return to the exercise of business activity with the forgiveness of debts and the protection of work, in the end, what protects is the very dignity of the human person, since it is through work that both the entrepreneur and the worker guarantee their livelihood.